2010
DOI: 10.1080/00224491003739993
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religion in Shaping Sexual Frequency and Satisfaction: Evidence from Married and Unmarried Older Adults

Abstract: This study assesses the role of religion in influencing sexual frequency and satisfaction among older married adults and sexual activity among older unmarried adults. We propose and test several hypotheses about the relationship between religion and sex among these two groups of older Americans, using nationally representative data from the National Social Life, Health, and Aging Project (NSHAP). Results suggest that among married older adults, religion is largely unrelated with sexual frequency and satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 32 publications
5
55
1
2
Order By: Relevance
“…However, some studies, have failed to replicate these finding, pointing to the importance of studying both biological and sociocultural mechanisms underlying the negative association between age and sexual satisfaction (Neto & Pinto, 2012;Thompson et al, 2011). Another consistent finding is that aging men report higher ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 15 levels of sexual satisfaction and sexual well-being than aging women (Kim & Jeon, 2013;Laumann et al, 2006;McFarland et al, 2011;Traeen & Schaller, 2010).…”
Section: Age-related Dynamics Of Sexual Satisfactionmentioning
confidence: 70%
See 4 more Smart Citations
“…However, some studies, have failed to replicate these finding, pointing to the importance of studying both biological and sociocultural mechanisms underlying the negative association between age and sexual satisfaction (Neto & Pinto, 2012;Thompson et al, 2011). Another consistent finding is that aging men report higher ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 15 levels of sexual satisfaction and sexual well-being than aging women (Kim & Jeon, 2013;Laumann et al, 2006;McFarland et al, 2011;Traeen & Schaller, 2010).…”
Section: Age-related Dynamics Of Sexual Satisfactionmentioning
confidence: 70%
“…Several cross-cultural studies have found that sexual satisfaction and overall sexual wellbeing diminish with age (Chao et al, 2011;del Mar Sánchez-Fuentes & Sierra, 2014;Dijkstra & Barelds, 2011;Field et al, 2013;Graf & Patrick, 2014;McFarland, Uecker, & Regnerus, 2011;Schick et al, 2010;Traeen & Schaller, 2010). However, some studies, have failed to replicate these finding, pointing to the importance of studying both biological and sociocultural mechanisms underlying the negative association between age and sexual satisfaction (Neto & Pinto, 2012;Thompson et al, 2011).…”
Section: Age-related Dynamics Of Sexual Satisfactionmentioning
confidence: 71%
See 3 more Smart Citations